2018
DOI: 10.1007/s12024-018-9967-9
|View full text |Cite
|
Sign up to set email alerts
|

Lethal endomyocarditis caused by chronic “Krokodil” intoxication

Abstract: "Krokodil" is a home-made opioid drug obtained by synthesizing desomorphine from codeine and combining it with other low-cost additives. Initially introduced in the former Soviet countries, it was then imported to Western Europe as a heroin substitute. To our knowledge, this is the first report of an Italian case of lethal krokodil abuse, that occurred in a 39-year-old man, who died suddenly after transportation to the Emergency Department (ED) for hyperthermia associated with sweating, dyspnoea and tachycardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Although heroin has been shown to cause oxidative stressinduced myocarditis, heroin did not affect the LV function in this AP4C -apical 4-chamber, AP2C -apical 2-chambers, SAX-B -short-axis basal, SAX-M -short-axis medial, SAX-A -short-axis apical study (16)(17)(18). Therefore, if there is no other risk factor to disrupt cardiac functioning (e.g., alcohol use), the use of heroin alone may not result in impairment of the LV function.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although heroin has been shown to cause oxidative stressinduced myocarditis, heroin did not affect the LV function in this AP4C -apical 4-chamber, AP2C -apical 2-chambers, SAX-B -short-axis basal, SAX-M -short-axis medial, SAX-A -short-axis apical study (16)(17)(18). Therefore, if there is no other risk factor to disrupt cardiac functioning (e.g., alcohol use), the use of heroin alone may not result in impairment of the LV function.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, biochemical studies have shown creatine kinase, creatine kinase-MB, and uric acid changes. Significant alteration in the levels of reduced and oxidized glutathione in the kidney and heart suggest that oxidative stress may be involved in krokodil-mediated toxicity (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of opioid receptors in the heart and their cross-talk to the cardiac β-adrenergic receptors might explain the cardiac vascular side effects caused by chronic opioid abuse [ 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since its appearance in Russia, the drug quickly spread to other neighboring former Soviet republics, especially Ukraine (which had around 20 000 cases in 2011), , as well as Georgia, Armenia, , and Kazakhstan. , The first western European country to report cases of krokodil use was Germany in 2011 . Subsequently, cases (both confirmed and suspected) have been reported in other European countries, such as France, Italy, Norway, Spain, and Poland, , with a significant part of them imported from Eastern Europe through immigrants from former Soviet republics . It is noteworthy that various reviews mention cases reported in the Czech Republic, Sweden, Belgium, and Portugal, ,,, but reliable information about these cases could not be found by the authors of the current review.…”
Section: Desomorphine (Krokodil)mentioning
confidence: 99%